Emma Corwin: capstone - Corwin, Emma, artist (Colorado State University. Libraries, 2021)
The artist's statement: What is a pilgrimage? A pilgrimage is a journey of devotion. It is a search for transformation. It is not easy or simple. The destination is not always direct. There are religious pilgrimages, but there are also individual pilgrimages, and pilgrimages that seek cultural and systemic progress. My journey through this series has been a pilgrimage, just as the modern day social movements to end hate and racism should be regarded as such. This series explores different journeys of devotion on micro and macro scales. This is my capstone series of oil paintings on canvas. I challenged my process and tried to break the conventional approaches I typically take in the studio. The speed and application varied and the solutions that arose relied on balance; a balance between energetic and controlled compositions, a balance between flat and organic marks, a balance between delicate and abrasive applications and colors. This balance was echoed in the broader theme of pilgrimages to reflect the energy they possess. Through this series, the application of paint on canvas and the ability to identify marks and process became more important to me than the readability of subject matter. It is about the inside energy and emotions behind these pilgrimages. This series is an ongoing quest for recognition and transformation in journeys of devotion.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting